Sobre la disponibilidad del nombre Cuniculus hernandezi Castro, López y Becerra, 2010 (Rodentia: Cuniculidae) (2014)
ABSTRACT: In this article we discuss the reasons why the bin omen Cuniculus hernandezi Castro, López y Bercerra, 2010, is not an available name according to the rules of the current International Code of Zoological Nomenclature (ICZN). Among these reasons are the lack of a precise description of the taxon and the failure to identify a type specimen. In addition, we highlight problems in the research design of the description of the bin omen that affect the conclusions regarding the taxonomic distinctiveness between the populations of the populations of the Oriental and Cental Cordilleras of Colombia.